Portfolio Rebalancing and the Turn‐of‐the‐Year Effect - RITTER, JAY R.; CHOPRA, NAVIN (Journal of Finance, 1989)
ABSTRACT This paper finds that, for the 1935–1986 period, the market's risk‐return relation does not have a January seasonal. The findings differ from those of other studies due to the use of value‐weighted, rather than equally weighted, portfolios. Inferences are sensitive to the weighting procedure because of the small‐firm return patterns in January. In particular, even in those Januaries for which the market return is negative, small‐firm returns are positive, and they are more positive the higher is beta. This is consistent with the portfolio rebalancing explanation of the turn‐of‐the‐year effect.